Atuação docente no contexto socioeducativo: investigação da educação na medida de internação - Scalvi, Gustavo Fernandes (Universidade Federal de São Carlos, 2025)
The comprehension of what defines infancy and adolescence comes from considering their social and historical construction. In Brazil, legal advances are noticeable, primarily established in the Estatuto da Criança e do Adolescente and in the paradigm of integral protection, which consider children and adolescents as people in development, endowed with rights and fundamental guarantees. However, old issues persist, especially when looking at the socio-educational measures system, where young black and poor people are the majority in situations of restriction or deprivation of liberty. Considering the legal premises that advocate for the socio-educational measure as eminently pedagogical, this work seeks to investigate the teacher’s role in the socio-educational context. In Study 1, an integrative literature review was conducted based on the combination of descriptors in the Scielo, BVS, and CAPES databases about the production of evidence regarding teaching in socio-education, with 17 articles being selected. The results point to several issues, especially those related to the development of specific policies, adequate working conditions, and initial and continuous training. On the other hand, recent studies were found that approach the concept of education as a mechanism of (re)insertion into society and the development of innovative pedagogical practices specific to the context. In Study 2, through the online application of a quantitative-qualitative questionnaire with 19 teachers from the Fundação CASA, the aim was to study the role of educators in the internment measure in the state of São Paulo. The results indicate a lack of prior preparation for the work, the need for constant adaptation, demotivation, and disinterest from adolescents, age-series distortion, limitations in some materials, and mainly, the lack of consensus regarding the primary function of the socio-educational measure. On the other hand, most participants believe that the school can function within the context of deprivation of liberty and are satisfied with the work done, emphasizing their central role in the educational process. Finally, the general discussion aims to relate Studies 1 and 2, reflecting on the results found and current topics relevant to the development of the field, while seeking an initial dialogue on possible interventions in light of Behavior Analysis, considering the development of adapted and specific strategies to help reduce and overcome the problems identified.
Teacher's role in the socio-educational context: investigation of education in the measure of deprivation of liberty
Keywords: Atuação docente; Socioeducação; Medidas socioeducativas; Privação de liberdade; Análise do comportamento; CIENCIAS HUMANAS::PSICOLOGIA; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO::PSICOLOGIA EDUCACIONAL